Estimating Smart Grid’s Carbon Emission Reduction Potential in China’s Manufacturing Industry Based on Decomposition Analysis - Fu, Hua; Shi, Yingying; Zeng, Yongchao (Frontiers in Energy Research, 2021)
China has a large manufacturing industry and shoulders the responsibility of reducing carbon emissions. Smart grid technologies can integrate multiple renewable energy technologies, which possess significant potential in reducing carbon emissions. To estimate the carbon emission reduction potential of the smart grid in China’s manufacturing industry, this paper applies a temporal logarithmic mean Divisia index (LMDI) method to analyze the driving forces of carbon emission changes in the whole manufacturing industry and 28 sub-industries from 2000 to 2017, respectively. The results reveal that industrial activity and energy intensity are the key factors leading to the increase and mitigation of carbon emissions, respectively. Sub-industries with high emission intensity are crucial for the reduction of carbon emissions in the manufacturing industry. By applying a smart grid, the carbon emissions could be reduced by 27.51% in the optimistic scenario.